A solution of subordinate vertices for quality connections of external free-form concrete panels - Lim, Jeeyoung; Son, Seunghyun; Kim, Do Yeong; Fitriani, Heni; Kim, Sunkuk (Journal of Civil Engineering and Management, 2018)
3D-designs of free-form buildings are developed using a computer due to difficulty of shape implementation. When producing free-form concrete panel (FCP) using materials such as GFRC (glass fiber reinforced concrete), engineers or manufacturers should precisely calculate the offset value or geometry of each member at the junction point of three or more FCPs before it is constructed. However, it is difficult to calculate offset geometry easily and quickly, and no research has been conducted on this topic. Therefore, the objective of this paper is to develop a solution of subordinate vertices for quality connections of external free-form concrete panels. The developed mathematical solutions practically support the production of FCPs with precise installation to ensure aesthetic quality of the building. This paper academically contributes to the automatic creation of joint details of FCPs implemented by BIM.